2022
DOI: 10.17159/sajs.2022/9514
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of the bioactive compounds from the edible fruits and leaves of Ficus sur Forssk. (Moraceae)

Abstract: Ficus sur Forssk. (Moraceae) is a medicinal plant species found in Africa and the leaves are used in traditional medicine as a blood builder to boost iron levels for the treatment of anaemia, skin disorders and sexually transmitted diseases. In this study, a phytochemical investigation was conducted on F. sur and the antioxidant properties of the isolates and extracts were evaluated. The major secondary metabolites that were isolated from the fruits and leaves were the triterpenoid (lupeol), sterol (β-sitoster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…The long range HMBC, H-H COSY and NOE correlations showed that the compounds is a dimer of catechin and 2''',4''',6'''-benzentriol-(7''-hydroxylphenyl)-2'',3''-dihydroxylpropyl. The HMBC correlations from proton at δH 4.56 (H-2) with carbons at δC 27.9 (C-4), 67.5 (C-3), 114.8 (C-2'), 131.5 (C-1'), 119.2 (C-6') and 156.2 (C-8a); δH 2.92/2.52 (H-4) with 67.5 (C-3), 81.8 (C-2), 99.7 (C-4a), and 155.9 (C-5); δH 5.92 (H-6) with carbons at δC 99.7 (C-4a), 155.9 (C-5) and 94.8 (C-8); δH 5.89 (H-8) with carbons at δC 94.8 (C-6), 99.7(C-4a), and 156.3(C-7); δH 6.92 (H-2') with carbon at 81.8 (C-2), 119.2 (C-6') and 144.9 (C-3'); δH 6.80 (H-5') with carbon at 81.1 (C-2), 131.5 (C-1'), 114.8 (C-2') and δH 6.77 (H-6') with carbon at 144.4 (C-4') and 114.4 (C-5') suggested catechin skeleton [11][12][13]. Key HMBC correlations of proton at δH 6.92 (H-2') with 81.8 (C-2), 119.2 (C-6') and 144.8 (C-6'') confirm the position of the side chain at C-3'.…”
Section: Resultsmentioning
confidence: 99%
“…The long range HMBC, H-H COSY and NOE correlations showed that the compounds is a dimer of catechin and 2''',4''',6'''-benzentriol-(7''-hydroxylphenyl)-2'',3''-dihydroxylpropyl. The HMBC correlations from proton at δH 4.56 (H-2) with carbons at δC 27.9 (C-4), 67.5 (C-3), 114.8 (C-2'), 131.5 (C-1'), 119.2 (C-6') and 156.2 (C-8a); δH 2.92/2.52 (H-4) with 67.5 (C-3), 81.8 (C-2), 99.7 (C-4a), and 155.9 (C-5); δH 5.92 (H-6) with carbons at δC 99.7 (C-4a), 155.9 (C-5) and 94.8 (C-8); δH 5.89 (H-8) with carbons at δC 94.8 (C-6), 99.7(C-4a), and 156.3(C-7); δH 6.92 (H-2') with carbon at 81.8 (C-2), 119.2 (C-6') and 144.9 (C-3'); δH 6.80 (H-5') with carbon at 81.1 (C-2), 131.5 (C-1'), 114.8 (C-2') and δH 6.77 (H-6') with carbon at 144.4 (C-4') and 114.4 (C-5') suggested catechin skeleton [11][12][13]. Key HMBC correlations of proton at δH 6.92 (H-2') with 81.8 (C-2), 119.2 (C-6') and 144.8 (C-6'') confirm the position of the side chain at C-3'.…”
Section: Resultsmentioning
confidence: 99%
“…Six compounds were isolated from Ficus microcarpa bark previously [13]. These were: (1) protocatechuic acid [14], (2) catechin [15,16], (3) chlorogenic acid, (4) methyl chlorogenate [14], (5) Procynandin B1 [17], and (6) procyanidin B3 [18]; moreover, four known compounds were isolated for the first time from F. retusa bark, namely: (7) catechin-3-O-glucoside [19], (8) isoferuyl quinic acid [20], (9) syringic acid [21], and (10) 7-O-Methyl-genistein [22].…”
Section: Identification Of Isolated Compounds From F Retusa Bark Acet...mentioning
confidence: 99%
“…Several species of Ficus are utilized in traditional medicine for their anti-inflammatory, anti-tumor, and tonic properties. These species have a long history of being used as medicinal remedies (Kitajima et al, 1999;Ogunlaja et al, 2022;Khan et al, 2022). Ficus extracts have been reported to have potential benefits in treating a variety of diseases, including epilepsy, jaundice, influenza, whooping cough, tonsillitis, bronchitis, enteritis, bacillary dysentery, toothache, and bruises (Kitajima et al, 1999).…”
Section: Introductionmentioning
confidence: 99%